Eccentric observation of total hardness in Lohara Village, Chandrapur District, Central India - Kamble, RK (International Journal of Environment, 2014)
The potability of water is judged by its physical, chemical and biological analysis. While analysing the water quality of Chandrapur district for winter 2012, summer 2013 and post-monsoon 2013 an eccentric observation was observed for total hardness estimation from the groundwater sample of Lohara village. While performing total hardness of groundwater sample by EDTA complexomertirc titration, after addition of buffer and inhibitor solution followed by Eriochrome Black T indicator a blue colour was formed instead of wine red colour. This observation was reported from all three sampling seasons. Perhaps, this may be the first time that such an observation was reported in the scientific literature. However, calcium hardness was found to be 84 ppm as CaCO3 in all three sampling season. DOI: http://dx.doi.org/10.3126/ije.v3i1.9950 International Journal of Environment Vol.3(1) 2014: 134-140